Five-year follow-up of a cluster-randomized controlled trial of a client-centred activities of daily living intervention for people with stroke. (February 2019) - Hedman, Annicka; Eriksson, Gunilla; von Koch, Lena; Guidetti, Susanne
Objective: To compare five-year outcomes and changes over time of a client-centred activities of daily living (ADL) intervention versus usual ADL interventions for people with stroke and their significant others. Design: Five-year follow-up of a cluster-randomized controlled trial where a client-centred ADL intervention ( n  = 129) or usual ADL interventions ( n  = 151) were delivered to people with stroke. Setting: Multicentre study including 16 inpatient or home-based rehabilitation units. Participants: People with stroke and significant others. Intervention: The client-centred ADL intervention aimed at enabling agency in daily activities and participation in everyday life and at reducing caregiver burden. Main measures: For people with stroke, perceived participation (Stroke Impact Scale), independence in ADL, life satisfaction, and use of formal/informal care were measured. For significant others, caregiver burden, life satisfaction, and mood (Hospital Anxiety and Depression Scale) were assessed. Results: Five years post-intervention, data were collected from 145 people with stroke (intervention group: n  = 71/control group: n  = 74) and 75 significant others (intervention group: n  = 36/control group: n  = 39). For those with stroke, the Participation domain of the Stroke Impact Scale showed no group differences at year five (68.9 vs 75.4, P  = 0.062) or in changes over time. At year five, the control group had better outcomes regarding Other help/supervision. Significant others in the control group were more likely to show signs of depression at year five (odds ratio = 22.3; P  < 0.001). Conclusion: The client-centred ADL intervention appears to render similar long-term effects as usual ADL interventions for people with stroke, but for significant others signs of depression might be reduced.